Preparation of Biomaterials Using Fish Collagen and Seaweed Alginate to Promote in-vivo Cell Growth and Proliferation Activity - Woo, Mun Jeng (2019)
Biomaterials have long been used as medical implants in humans to increase the rate of healing and prolong patient lifespan. The material of choice for the fabrication of biomaterials mimic the ECM (extracellular matrix) of humans, such as animal sourced collagen. The main source of collagen from animals are usually from bovine and porcine skin and bone wastes. However, due to local religious and cultural sensitivities in Malaysia, therefore limited research has been carried out on bovine and porcine sourced collagen. Little research has been directed towards using fish waste as a source of collagen, specifically from local fish sources. Therefore, this study was carried out to investigate the feasibility of using collagen extracted from fish waste of the local fish processing industry, specifically the skin waste of Nile tilapia (Oreochromis niloticus sp) and hybridising it with sodium alginate from the Sargassum Polycystum sp seaweed which is found in abundance along the coastal areas ofPort Dickson, Malaysia for the fabrication of biomaterials. Samples of Nile Tilapia skin waste were obtained from the wet market in Bandar Sungai Long, and collagen was extracted using pH 3.25 acetic acid at 0.5 M. Sodium alginate has been used in the fabrication of biomaterials due to it’s biocompatibility with the ECM of humans and ease of gelation. The biomaterials were fabricated with different ratios of collagen to sodium alginate. FTIR (Fourier Transform Infrared Spectroscopy) analysis proved that collagen was successfully extracted while HPLC (High Performance Liquid Chromatography) showed that the collagen from Nile Tilapia is rich in imino acids hydroxyproline, proline and glycine. Polyacrylamide gel electrophoresis, in the presence of 10 % SDS using 7.5 % stacking gel illustrated a doublet pattern for α1 and α2 chains (at approximately 120 kDa to 125 kDa) and a β chain (approximately 220 kDa). Swelling ratio test demonstrated the hydrophilic nature of the biomaterials fabricated with higher ratio of sodium alginate to collagen, namely the 30% C : 70% SA with 12.75 % swelling ratio as compared to 90% C : 10% SA with 0.04% swelling ratio. SEM (Scanning Electron Microscope) showed the highly porous surface morphology of the fabricated biomaterials, particularly the pure sodium alginate and 50%C : 50% SA biomaterial. Results of the Trypan Blue Staining, MTT assay ((3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide)) and direct contact test demonstrated that the fabricated biomaterials had a positive impact on cell growth and proliferation activity.From the MTT assay results, it is shown that cell growth rates and proliferation activity were higher when cultured with fabricated biomaterials as compared to the control. The 80%C : 20%SA had the highest percentage viability around 30 % on Day 2, while control only had around 15 %. On Day 4, the 80 % C: 20 % SA biomaterial reached almost 95 % viability as compared to the control which only achieved around 50% viability. In conclusion, the hybridised biomaterials maybe used to enhance cell growth and proliferation activity. Biomaterials fabricated with higher ratios of sodium alginate to collagen demonstrated optimum cell growth and proliferation activity.